(untitled) (Journal of actual problems of jurisprudence, 2018)
The article analyzes the ethical issues in the implementation of the categories of criminal proceedings. Focuses on the changes made to the criminal trial the new legislation. Considered tasks and powers of the subjects of criminal proceedings arising from the principles of the criminal process. A comparative analysis of the previous legislation. Key words: criminal procedure, category of ethics, ethics, ethics of justice, the subjects of criminal proceedings, the ethics of law enforcement.